Is there any relationship between PSA and increased peripheral CD4+CD25highFOX3+ Treg in prostate cancer patients? - Yigit Akin; Sadi Koksoy; Selcuk Yucel; Tibet Erdogru; Mehmet Baykara (Journal of Health Sciences, 2011)
Introduction: The aims of this study were fi rst, to determine whether peripheral levels of CD4+CD25highFoxp3+ regulatory T cells (Treg) are elevated in Prostate Cancer (PCa) patients, and second, to determine the direct correlation between peripheral Treg and total serum Prostate Specifi c Antigen (PSA) levels in these patients. Methods: Peripheral Blood Mononuclear Cells from 56 subjects undergoing diagnostic prostate biopsies (PSA ≥ 2.5 ng/ml) were analyzed for Treg numbers. The association between the peripheral Treg and serum PSA values was fi rst determined in the entire population, including people with no prostate pathology and PCa and Benign Prostate Hyperplasia (BPH) patients, and second, in nine PCa patients before and after curative prostatectomy. Results: This project was performed in Akdeniz University immunology laboratory and urology out patient clinic from 2008 to 2010. Peripheral Treg frequencies were signifi cantly increased in PCa patients (n = 19, 3.23 ± 1.59) compared with BPH patients (n = 27, 1.66 ± 0.80) and healthy subjects (n = 10, 1.08 ± 0.43) (p < 0.01). The percentage of Treg in BPH patients was also signifi cantly higher than that of healthy subjects (p < 0.01). Importantly, the increase in BPH and PCa patients paralleled the elevation in total serum PSA levels, demonstrating a strong positive correlation (r = 0.75; p < 0.01). Conclusion: These results demonstrate that peripheral Treg densities are correlated with PSA in BPH and PCa patients, suggesting that PSA may have a role in Treg induction and/or maintenance in Treg in these people.